In Silico Design & Development of Some Selected Flavonols Against Beta–Glucuronidase Inhibitory Activity - Sovan Pattanaik,; Sudam Chandra Si,; Sudhanshu Sekhar Rout,; Anindya Bose ,; Siva Shankar Nayak, (Journal of Pharmacy and Nutrition Sciences, 2015)
Drug discovery process develops faster due to more advances in computational techniques. The protein ligand interaction well predicted due to the in-silico approach study. The present investigation focused towards the development of lead structure for treatment of hepatic disorders. An increase in serum acid hydrolase, including β-glucuronidase has been reported in numbers of pathological conditions such as arthritis, renal diseases and epilepsies. Enhancement of this enzyme β–glucuronidase in blood has been found to correlate significantly with liver damage. β-glucuronidase inhibitor is a novel approach which is different from the available hepatoprotective drug therapies. Method: The current study is based on in-silico ligand screening and in-vitro estimation of the three flavonols [Naringenin, Quercetin and 2-(3, 4-Dihydroxy Phenyl)-7-Hydroxy-3-(2-Hydroxy Ethoxy) 4-H-Chromen-4one] compounds with enzyme β-glucuronidase. Molecular docking software Py Rex and Py Mol was used to dock the selected ligand in the binding site of the crystal structure of protein. Results: Docking results are based on the least binding energy of the selected flavonols compounds. Further attempt has been made towards in-vitro estimation of this enzyme with those selected compounds. The binding affinity with existence of hydrogen bonds leads to find out the mechanism which was well correlated with the findings of in-vitro inhibitory activity. Conclusion: The result outcome of the binding orientation of 2-(3, 4-Dihydroxy Phenyl)-7-Hydroxy-3-(2-Hydroxy Ethoxy) 4-H-Chromen-4one linked with the active amino acid residue of the protein and the binding affinity leads to find out the mechanism for its potential in-vitro inhibitory activity.